Obtenção de néctar de banana por maceração enzimática de polpa da variedade prata-anã - Rodrigues, Renata Débora Pinto (2013)
Banana is the second most widely produced fruit in Brazil. The popularity of the banana is due to their nutritional and sensory aspects. The absence of hard seeds and juice in the pulp, and their availability throughout the year, also contribute to its acceptance. Currently, there is a greater concern for the consumers to purchase processed products with sensory characteristics close to fresh food, which has motivated the use of tropical fruits similar. The processing is presented as an alternative to the use of surplus fruit representing a way to increase the shelf life and add value to the product. Among the various fruit similar, highlight the nectar. The Brazilian market for juices and nectars ready to drink is booming, following the global trend of consumption beverages and convenient healthy. In this study, we evaluated the impact of the addition of commercial enzymes on the characteristics of banana puree Silver Dwarf, aiming to reduce its consistency and thus enable the industrialization of nectar. It used of 75 µL of commercial enzyme preparations: AMG 300L, Celluclast 1.5 L, XXL Pectinex, singly and in combination. The efficiency of enzymatic maceration of banana pulp was assessed in terms of consistency analysis, the total content of reducing groups (GRT), titratable acidity (TA) and quantification of soluble solids (SS). The addition of enzymes to the pulp maceration of bananas played a major role in increasing the sugar concentration and decreased viscosity. The evaluation of nectars, made from the pulp macerated, revealed that the samples were well accepted, with averages situated around the mode 6 (like slightly).